The Determinants Of Earnings Persistence In The Financial Times Stock Exchange (FTSE) ASEAN Star - Saputera, Denny; Wijaya, John Henry; Ichsani, Sakina (Technium Business and Management, 2024)
This study aims to identify the factors that can influence earnings persistence in companies listed on the Financial Times Stock Exchange (FTSE) Asean Star in 2021-2022, with a total sample of 30 companies, comprising 3 companies per country from Indonesia, Malaysia, Singapore, Thailand, and the Philippines. The variables included in this study to influence earnings persistence are Accrual Reliability, Cash Flow Volatility, Sales Volatility, Firm Size, and Debt Level. The results show that Accrual Reliability, Cash Flow Volatility, Sales Volatility, and Firm Size have a partial impact on Earnings Persistence, while Leverage does not affect Earnings Persistence. The simultaneous test results indicate that Accrual Reliability, Cash Flow Volatility, Sales Volatility, Company Size, and Debt Lavel together have a significant effect on Earnings Persistence.